Gas-liquid chromatography in routine processing of blood cultures for detecting anaerobic bacteraemia. Issue 2 (February 1981) - Reig, M; Molina, D; Loza, E; Ledesma, M A; Meseguer, M A
Abstract : Gas-liquid chromatography was performed on 233 positive blood cultures and findings were compared with culture results. Obligate anaerobic bacteria were recovered from 78 out of 79 blood cultures containing butyric or iso-valeric acids, or both; from 28 out of 69 blood cultures containing succinic acid; and from only one out of 41 blood cultures containing succinic but not butyric or iso-valeric acid. Good correlations (88%) were found for the recovery of anaerobic bacteria and the detection of butyric and/or iso-valeric acids. Detecting volatile fatty acids by gas-liquid chromatography performed on blood cultures at the first signs of growth can therefore provide an early and reliable indication of the presence of anaerobic bacteria.